ANALISIS BIBLIOMETRIK: FOKUS PENELITIAN CRITICAL THINKING DALAM PEMBELAJARAN MATEMATIKA (2017 – 2022) - Ilham Muhammad; Dika Faiz Himmawan; Syifa Mardliyah; Dadan Dasari (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2023)
Critical thinking can be formed in several ways, one of which is through the process of learning mathematics. This study aims to determine trends and research focus related to critical thinking in mathematics learning. A total of 327 data were obtained from database dimensions. VOSviewer software is used to display visualizations based on bibliographic pairs and events with keywords by the author. Researchers use qualitative research methods. The analysis technique used is descriptive bibliometric analysis and bibliometric visualization method. The results of the study show that the countries of Indonesia and the United States, the Indonesian University of Education and Padang State University, the "journal of physics conference series" and documents (Mutakinati et al., 2018) have been the most influential on critical thinking in learning mathematics in the last five years . The research focus is divided into four of them, namely: 1) STEM approach; 2) Learning with Problem-based learning; 3) Critical thinking in higher education; 4) learning outcomes and creative thinking. STEM is not directly related to geometry material, and problem-based learning is also not directly connected to independent learning.